Long-term course and morphological MRI correlates of cognitive function in multiple sclerosis. (May 2021) - Pinter, Daniela; Khalil, Michael; Pirpamer, Lukas; Damulina, Anna; Pichler, Alexander; Fruhwirth, Viktoria; Ropele, Stefan; Schmidt, Reinhold; Fuchs, Siegrid; Enzinger, Christian
Background: Cognitive impairment frequently occurs in patients with MS (pwMS). Magnetic resonance imaging (MRI) markers could help to identify patients at risk for decline. Objective: To characterize the long-term course and morphological MRI correlates of cognitive function in pwMS. Methods: We invited 116 pwMS who had undergone clinical, cognitive, and MRI evaluations between 2006 and 2012 (baseline, BL) to attend follow-up (FU) testing between 2016 and 2018. Disability (expanded disability status scale (EDSS)), cognition (brief repeatable battery of neuropsychological test (BRB-N)), global and regional T2-lesion load (T2-LL), brain volumes, and cortical thickness were assessed. Results: Sixty-three pwMS were willing to attend the FU (54%; median EDSS = 2, interquartile range (IQR) = 2) and did not differ from non-participating pwMS regarding BL characteristics. At BL, half of the participants showed cognitive deficits in at least one domain. Across the entire group, we observed no relevant changes in physical disability and cognition over 10 years. BL thalamic volume best predicted cognitive function at FU, in addition to age and BL cognition, explaining 67% of variance. Cognitive decliners (23.8%) were older, had longer disease duration, and a tendency for lower thalamic volume at BL. Conclusion: Thalamic volume predicted FU cognitive function and distinguished declining from stable pwMS, underlining the potential of MRI to define risk groups.